Study of the pharmacotechnological parameters of ginger rhizomes for developing the conditions extracting of extractive substances - Konovalenko, Ilona; Kriukova , Anna (Annals of Mechnikov’s Institute, 2023)
Introduction. Phytotherapy is a form of medicinal auxiliary therapy that meets all these requirements. The goal of phytotherapy is to influence the self-regulation processes of the human body. Typically, treatment with herbal preparations excludes side effects, and their high therapeutic activity has been substantiated by the results of fundamental research conducted by Ukrainian and international pharmacologists. Purpose of the study. Research on the pharmacotechnological properties of ginger rhizomes, including physicochemical investigations and extraction methods aiming to efficiently extract biologically active substances, has been conducted. Materials and methods. The objects of the study are ginger rhizomes (manufacturer "Medagroprom", Dnipro). Research methods: information–search, information–analytical, physico–chemical, pharmacotechnological (specific weight, bulk density, apparent density, porosity, heterogeneity of the material, free volume of the layer, angle of repose, water absorption coefficient). Results & Discussion. The conducted technological studies confirmed that the studied raw material is characterized by a high value of bulk mass and high diversity. Volumetric weight in the studied raw material had a value within 0.195 g/cm3. Free volume of the layer for ginger rhizomes had high values, which shows the need to use larger volumes of the extractant to wet the MPM and compact it when loading it into the extraction device. The difference between the specific and volumetric weight shows that the raw material occupies a large volume, as a result of which it is necessary to take into account when calculating the ratio of MPM and the finished product, choosing the size of the extractor, the features of loading the raw materials, etc. The water absorption coefficient was 1.55. This indicator is an important characteristic when calculating the amount of extractant in the subsequent production of liquid extract. The maximum level of extractives is ensured when obtaining a liquid extract with a raw material particle size of 1–3 mm, a ratio of raw materials and extractant – 1:10, extraction for 60–180 min at a temperature of 90 ± 5 °C, infusion until cooling – 30 min. Maceration is not an efficient, cost-effective method, and at the same time it is time-consuming, and the percolation method requires industrial capacities. At the same time, ethanol, as an extractant, is not an economically beneficial solvent compared to purified water. Conclusions. The main technological parameters of the medicinal plant raw material were determined, which confirmed that the ginger rhizomes are characterized by high values of porosity, free volume of the layer, bulk mass and low porosity of the raw material. On the basis of pharmacotechnological studies, the influence of extraction parameters was studied. It was determined that the optimal mode of extraction of the aqueous extract is infusion in a water bath (water temperature – 90 °C) for 60 minutes, infusion at room temperature until cooling - 30 minutes at a ratio of raw materials: extractant 1:10. Keywords: ginger rhizomes, pharmacotechnological properties, extraction.